DRAMATURGI PENGGUNAAN FITUR CLOSE FRIEND PADA MEDIA SOSIAL INSTAGRAM (Studi Kasus Pada Penggemar K-Pop Mahasiswa Universitas Trunojoyo Madura) - Kartika Ariyanti; Edy Purwanto (Universitas Trunojoyo Madura, 2023)
The purpose of this study is to understand the impressions displayed by K-Pop fans among the students of Trunojoyo University Madura as users of the Instagram social media platform, both in public and close friend Instagram Story posts. This research adopts a qualitative research design. The data collection methods used in this study include observation, interviews, and documentation. The research informants were selected using purposive sampling, and data analysis was conducted following Miles and Huberman's techniques.The results of this study reveal that the self-impressions displayed by K-Pop fans among Trunojoyo University Madura students in public Instagram Story posts include the impression of being happy, the impression of being non-fanatical K-Pop fans, and the impression of being individuals who have interests beyond K-Pop. On the other hand, the impressions displayed in close friend Instagram Story posts include the impression of not always being happy, the impression of being fanatical K-Pop fans, the impression of being funny, and the impression of being fans of K-Pop with a liking for vulgar content. The management of these impressions is carried out by selecting and editing the uploaded photos and videos, searching for quotes from K-Pop artists, and choosing K-Pop songs to be uploaded.